Language and the geopolitics of (dis)location: A study of Zimbabwean Shona and Ndebele speakers in Johannesburg. - SIZIBA, GUGULETHU; HILL, LLOYD (Language in Society, 2018)
The Zimbabwean diaspora is a well-documented phenomenon. While much research has been done on Zimbabwean migration to South Africa, the role that language plays in this process has not been well researched. This article draws on South African census data and qualitative fieldwork data to explore the manner in which Zimbabwean migrants use languages to appropriate spaces for themselves in the City of Johannesburg. The census data shows that African migrants tend to concentrate in the Johannesburg CBD, and fieldwork in this area reveals that Zimbabwean migrants are particularly well established in two suburbs--Yeoville and Hillbrow. The article explores migrant language repertoires, which include English, Shona, Ndebele, and a variant of Zulu. While many contributions to the migration literature tend to assume a strong association between language and ethnicity, the article shows how this relationship is mediated by geographic location and social positioning within the city. (Language, migration, Johannesburg, South Africa, Zimbabwe)